The eternal alliance of two worlds in William Ospina - Acevedo, Segura Yadira (Romanica Olomucensia, 2017)
The Amazon Trilogy, by the Colombian writer William Ospina, reconstructs one of the most amazing historical events in the history of humanity, the discovery of America. The author recreates the life of an emblematic character, though one forgotten by historians and chroniclers, in the colonization of America - the conquistador Pedro de Ursua. The topic of the conquest of America is projected in a transversal way throughout his writings. For this reason, when speaking about the eternal alliance of two worlds, it was necessary to study the creative and critical work of this writer on the basis of the theoretical ideas of important researchers such as Peirce, Todorov, Juan de Castellanos, O'Gorman, Gomez-Muller, Amodio, Gines de Sepulveda, and Carlos Fuentes, among others. Indeed, thanks to the theoretical contributions of these historians, chroniclers, semiologists, poets, and novelists it was possible to carry out a reconstruction of the conquest of America through the work of one of the most important writers in Colombian literature, in order to rescue the past in a more real and palpable way. So, rather than being contemplative readers, we were witnesses to the violent wars and the eternal alliances that our ancestors lived through, weeping with them for their dead and suffering their tragedies, feeling the rain and hearing the thunder, fascinated by their songs and listening to their cries of despair. In this paper it is concluded that the historical novels by William Ospina and some of his essays guide us towards an ontological reflection on America, as well as an approximation of the different meanings of the concept of culture and/or its epistemological threshold.
Keywords: William Ospina; the Amazon Trilogy; conquest of America; culture and transculturation; the unspeakable; the Other